ПРИВОДНІ УСТАНОВКИ СЕРЕДНЬОЇ ПОТУЖНОСТІ НА ОСНОВІ ІНВЕРТОРІВ ПОТРІЙНИХ ДЖЕРЕЛ НАПРУГИ З НАЛАШТУВАННЯМ АЛГОРИТМІВ СИНХРОННОЇ БАГАТОЗОННОЇ ШІМ - Олещук, В. (Інститут електродинаміки НАН України, Київ, 2024)
This paper presents short overview of the development and dissemination of specialized schemes and algorithms of space-vector-based synchronous multi-zone pulsewidth modulation (MZ PWM) for control of triple inverters of the medium-power variable speed drives characterized by relatively low switching frequency of inverters. It insures providing synchronization and symmetry of the basic voltage waveforms in triple-inverter-based configurations of drive installations on the base of standard voltage source inverters (VSIs). It assures also minimization of magnitudes of even-order harmonics and undesirable subharmonics in spectra of the basic voltages of drive installations, leading to reducing of losses in the corresponding apparatuses and to increasing of its efficiency. Examples of application of the basic techniques of multi-zone PWM for regulation of three typical structures of triple-VSI-based medium-power motor drives are presented. Modeling and simulations give a behavior of drive installations based on triple inverters adjusted by algorithms of synchronous MZ PWM. References 12, figures 11, table 1.